Impact-induced muscle damage and contact sports: Etiology, effects on neuromuscular function and recovery, and the modulating effects of adaptation and recovery strategies - Naughton, M.; Miller, J.; Slater, G. J. (International Journal of Sports Physiology and Performance, 2018)
Athletes involved in contact sports are habitually exposed to skeletal-muscle damage in their training and performance environments. This often leads to exercise-induced muscle damage (EIMD) resulting from repeated eccentric and/or high-intensity exercise and to impact-induced muscle damage (IIMD) resulting from collisions with opponents and the playing surface. While EIMD has been an area of extensive investigation, IIMD has received comparatively little research, with the magnitude and time frame of alterations following IIMD not presently well understood. It is currently thought that EIMD results from an overload of mechanical stress that causes ultrastructural damage to the cellular membrane constituents. Damage leads to compromised ability to produce force, which manifests immediately and persists for up to 14 d following exercise exposure. IIMD has been implicated in attenuated neuromuscular performance and recovery and in inflammatory processes, although the underlying course over time remains unclear. Exposure to EIMD leads to an adaptation to subsequent exposures, a phenomenon known as the repeated-bout effect. An analogous adaptation has been suggested to occur following IIMD; however, to date, this contention remains equivocal. While a considerable body of research has explored the efficacy of recovery strategies following EIMD, strategies promoting recovery from IIMD are limited to investigations using animal contusion models. Strategies such as cryotherapy and antioxidant supplementation that focus on attenuating the secondary inflammatory response may provide additional benefit in IIMD and are explored herein. Further research is required to first establish a model of generating IIMD and then explore broader areas around IIMD in athletic populations.